The experience of reproductive planning of female military firefighters - Elayne Arantes Elias; Letícia Becker Vieira; Tassiane Ferreira Langerdorf; Pilar Almansa Martinez; Ivis Emília de Oliveira Souza (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To understand the experience of reproductive planning of female military firefighter health professionals. Method: Phenomenological research under the theoretical-philosophical and methodological framework of Martin Heidegger. Developed in Fire Department units in Rio de Janeiro in the first half of 2016, with 21 female military health professionals. Results: Women expressed that it is necessary to work and manage roles. Therefore, they have to plan to have a child, due to the difficulty of managing all the tasks and reconciling motherhood with work. They think of a more comfortable situation to dedicate themselves to their children, since they are the main responsiblefor them. Conclusions: Comprehensive health actions for military women need to be included in public policies, as it is a group that has been increasingly participating in an environment previously restricted to men and with their characteristics.